The Beyond The Wheel: Encouraging Public Transport Acceptance in Palembang with Green Strategic - Al Fartzie, Hariman; Yulistarini, Dian; Fansyuri, Fansyuri (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2025)
Purpose This study aims to evaluate green economy strategies to enhance the adoption of public transportation in Palembang and provide policy recommendations. In this research, green economy strategies focus on optimizing the use of public transportation to reduce carbon emissions, improve energy efficiency, and develop a more sustainable and environmentally friendly transportation system. Methodology The research employs a quantitative approach, utilizing regression analysis, correlation, and ANOVA, supported by interviews with policymakers. Findings The results reveal a significant relationship between green economy strategies and public transportation acceptance. However, no significant differences were observed for certain groups of employees. Suggestion The findings of this study advocate for strengthening public transportation policies based on green economy principles to enhance public transportation acceptance.